Learn iPhone and iPad cocos2d Game Development - Itterheim, Steffen (Apress, 2012)
In May 2009 I made first contact. For the first time in my life, I was subjected to the Mac OS platform and started learning Xcode, Objective-C, and cocos2d. Even for an experienced developer, it was a struggle. It was at that time that I realized that cocos2d was good, but it lacked documentation, tutorials, and how-to articles—especially when compared with the other technologies I was learning at the time. Fast forward a year to May 2010. I had completed four cocos2d projects. My Objective-C and cocos2d had become fluent. It pained me to see how other developers were still struggling with the same basic issues and were falling victim to the same misconceptions that I did about a year earlier. The cocos2d documentation was still severely lacking. I knew that other developers using cocos2d were having great success attracting readers to their blogs by writing tutorials and sharing what they know about cocos2d. To date, most of the cocos2d documentation is actively being created in a decentralized fashion by other developers. I saw a need for a web site to channel all of the information that’s spread over so many different web sites. I created the www.learn-cocos2d.com web site to share what I knew about cocos2d and game development, to write tutorials and FAQs, and to redirect readers interested in cocos2d to all the important sources of information. In turn, I would be selling cocos2d-related products, hoping it might one day bring me close to the ultimate goal of becoming financially independent. The business model has been proven to work by many shining examples. And I enjoy helping others, having been the go-to guy in all companies I’ve worked for. I knew I could make the web site a win for everyone. I was excited.